Bitcoin's Position as a Digital Currency and Protection of Users According to Positive Law - Putri, Melisa; Mangar, Irma (Journal of Development Research, 2024)
Rapid technological advances have had a great impact on many aspects of human life, one of which is the economy. Judging from the all-digital era that has spread almost to all corners of the world, in this all-digital era bitcoin has emerged which is used as a digital medium of exchange. Bitcoin is a cryptocurrency that appeared precisely in 2009 by someone under the pseudonym Satoshi Nakamoto. The method used in this study is normative law research, by analyzing library materials and secondary data to collect information about regulations and literature that are considered relevant to the research topic. As a result, there are regulations that regulate the provisions of currency as a legal instrument of payment in Indonesia, namely in Law Number 7 of 2011 concerning the Rupiah Currency, so that only the rupiah currency can be used as a means of payment, due to this legal vacuum raises many question marks regarding the position of the use of the bitcoin currency, considering that this will lead to the aspect of legal protection that will be given to bitcoin users. If at one point there is a loss arising from the use of bitcoin, with the absence of specific regulations that regulate bitcoin, it means that the use of bitcoin cannot be said to be safe considering that its position has not been regulated by the government